Lip-Alg / GE / CHC composite hydrogel bead as well as preparation method and application thereof

By preparing Lip-Alg/GE/CHC composite hydrogel beads, the problems of poor immobilization of traditional Alg immobilization on lipase and low swelling rate are solved, and higher enzyme activity and swelling performance are achieved, which is suitable for gastrointestinal administration.

CN119587503APending Publication Date: 2025-03-11DALIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411767520.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Traditional Alg immobilization has poor immobilization effect on lipase and low swelling rate, which cannot effectively solve the release of lipase in the gastrointestinal tract.

Method used

The preparation method of Lip-Alg/GE/CHC composite hydrogel beads is adopted. By mixing the lipase solution with sodium alginate solution, adding chitosan hydrochloride and calcium chloride solution to form the composite hydrogel beads, which improves the immobilization effect and swelling performance of the lipase.

Benefits of technology

It significantly improves the enzyme activity and stability of lipase, enhances the swelling performance and pH response of hydrogel beads, and achieves more effective release of lipase in the intestine.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119587503A_ABST
    Figure CN119587503A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biochemical engineering and biology, in particular to a Lip-Alg / GE / CHC composite hydrogel bead as well as a preparation method and application thereof. And mixing a lipase solution with a sodium alginate solution to obtain a Lip-Alg / GE solution, mixing the Lip-Alg / GE solution with the mixed solution, and carrying out a stirring reaction after the hydrogel beads are formed to obtain the Lip-Alg / GE / CHC composite hydrogel beads. The method is simple and convenient to prepare, and compared with traditional sodium alginate immobilization, the pH responsiveness of the sodium alginate is reserved, the swelling property of the material is improved, and the enzyme activity recovery rate of lipase is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the fields of biochemical engineering and biotechnology, and in particular to a Lip-Alg / GE / CHC composite hydrogel bead and a preparation method and application thereof. Background Art

[0002] Lipase (Lip) is a digestive enzyme that converts triglycerides in fat into monoglycerides and two fatty acids, making them easier to digest and absorb by the intestines. Lip can also bring many benefits, such as solving nutrient deficiencies in patients with cystic fibrosis, helping to improve celiac disease, and optimizing the absorption of vitamins and minerals from food. Lip only works in the small intestine, and once Lip secretion is insufficient, there will be no source of compensation. After the decrease in pancreatic juice secretion occurs, insufficient Lip secretion occurs first. In addition, Lip is the most fragile digestive enzyme and can be decomposed by gastric acid, trypsin, and chymosin. Therefore, it is necessary to design a reasonable and effective drug delivery system to achieve the encapsulation of Lip and to deliver Lip.

[0003] Due to its superior physical and chemical properties, good biocompatibility and low price, hydrogels are widely used in the preparation of drug carriers. According to different classification methods, hydrogels can be divided into different types. Among them, according to the responsiveness to the environment, they are divided into environmentally responsive hydrogels and environmentally non-responsive hydrogels. Environmentally responsive hydrogels, also known as smart hydrogels, refer to hydrogels that change their own structure and properties according to environmental changes, such as light-responsive hydrogels, temperature-responsive hydrogels, pH-responsive hydrogels, etc. Due to the large pH changes in the human gastrointestinal tract, pH-responsive hydrogels are more suitable for gastrointestinal administration.

[0004] Traditional Alg immobilization has the disadvantages of poor immobilization effect on Lip and low swelling rate. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a Lip-Alg / GE / CHC composite hydrogel bead and a preparation method and application thereof, which improves the defects of poor immobilization effect and low swelling rate of Alg as an immobilization carrier on Lip.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing Lip-Alg / GE / CHC composite hydrogel beads, comprising the following steps:

[0008] 1) mixing the lipase solution with the sodium alginate solution to obtain a Lip-Alg / GE solution;

[0009] The volume ratio of the lipase solution to the sodium alginate solution is 1:4;

[0010] The lipase activity in the lipase solution is 50 U / mL;

[0011] The mass concentration of sodium alginate in the sodium alginate solution is 1.5-2.5%, and the mass concentration of gelatin is 0.1-1%;

[0012] 2) mixing the Lip-Alg / GE solution obtained in step 1) with the mixed solution, and stirring and reacting after the hydrogel beads are formed to obtain Lip-Alg / GE / CHC composite hydrogel beads;

[0013] The mixed solution is obtained by mixing a chitosan hydrochloride solution and a calcium chloride solution;

[0014] The mass concentration of the chitosan hydrochloride solution is 0.5-2%;

[0015] The mass concentration of the calcium chloride solution is 2-6%;

[0016] The volume ratio of the chitosan hydrochloride solution to the calcium chloride solution is 1:4;

[0017] The volume ratio of the mixed solution to the sodium alginate solution is 10:0.8.

[0018] Preferably, in the sodium alginate solution in step 1), the mass concentration of sodium alginate is 2%, and the mass concentration of gelatin is 0.5%.

[0019] Preferably, the mass concentration of the chitosan hydrochloride solution in step 2) is 1%;

[0020] The mass concentration of the calcium chloride solution is 4%.

[0021] Preferably, in the step 1), the mass concentration of sodium alginate in the sodium alginate solution is 1.5%, and the mass concentration of gelatin is 1%;

[0022] The mass concentration of the chitosan hydrochloride solution in step 2) is 2%, and the mass concentration of the calcium chloride solution is 6%.

[0023] Preferably, in the step 1), the mass concentration of sodium alginate in the sodium alginate solution is 2.5%, and the mass concentration of gelatin is 1%;

[0024] The mass concentration of the chitosan hydrochloride solution in step 2) is 1%, and the mass concentration of the calcium chloride solution is 2%.

[0025] Preferably, in the step 1), the mass concentration of sodium alginate in the sodium alginate solution is 2%, and the mass concentration of gelatin is 0.5%;

[0026] The mass concentration of the chitosan hydrochloride solution in step 2) is 1%, and the mass concentration of the calcium chloride solution is 4%.

[0027] Preferably, the stirring reaction time in step 1) is 20 minutes and the temperature is 0-4°C.

[0028] The present invention also provides Lip-Alg / GE / CHC composite hydrogel beads prepared by the preparation method described in the above technical solution.

[0029] The present invention also provides the use of the Lip-Alg / GE / CHC composite hydrogel beads described in the above technical solution in improving the swelling performance of the hydrogel beads.

[0030] The present invention also provides the use of the Lip-Alg / GE / CHC composite hydrogel beads described in the above technical solution in improving the lipase activity of the hydrogel beads.

[0031] Sodium alginate (Alg) is one of the most widely used pH-responsive hydrogels, mainly extracted from brown algae such as kelp or sargassum. It is mainly composed of two unit structures, β-D-mannuronic acid (M unit) and α-L-guluronic acid (G unit), and is connected by β-1,4-glycosidic bonds to form GM, MM and GG fragments in different proportions to form copolymers. 2+ It can form a calcium alginate gel network, which is more tightly cross-linked in an acidic environment. The drug is mainly released by diffusion, and the speed is slow. 2+ The crosslinking with Alg dissociates, and the drug release rate is accelerated. In addition, there are carboxyl groups on the gel network, which can sense changes in pH and show swelling or shrinkage. When pH>pKa value, the carboxyl group ionizes to COO -, which leads to an increase in the electrostatic repulsion between the chains, an increase in the gaps in the gel network, and the gel's ability to absorb a large amount of water, forming a very loose structure. When pH < pKa, the carboxylic acid group is -COOH, and the gel network contracts, forming a very tight structure. Utilizing the pH responsiveness of Alg, an intestinal-targeted drug carrier can be prepared. However, the simple encapsulation method using Alg alone has problems such as low mechanical strength, low encapsulation efficiency, and unsatisfactory enzyme leaching and enzyme recovery. Therefore, Alg is often used in combination with other materials to achieve better encapsulation of drugs. Gelatine (GE) is produced by partial hydrolysis of collagen and is a component of animal connective tissues, bones, and skin coatings. GE is similar to the extracellular matrix and can promote cell adhesion, proliferation, and differentiation, has biocompatibility, biodegradability, and low cytotoxicity, and is suitable for 3D bioprinting technology and regenerative medicine in tissue engineering. In addition, GE can transport drugs, genes, and cells. As a drug carrier, GE can provide mild conditions for maintaining the activity of biomacromolecule drugs (such as proteins, oligopeptides, and polypeptides). Chitosan is a natural polycationic polysaccharide that can interact with negatively charged polymers and has adhesiveness due to the intermolecular attraction formed by electrostatics. Chitosan is soluble in weak acids, so its use as a controlled-release carrier for proteins, polypeptides, and vaccines is beneficial for maintaining the biological activity of protein and peptide drugs. As a water-soluble derivative of chitosan, chitosanhydrochloride (CHC) combines the inherent properties of chitosan and has excellent water solubility at neutral pH. Therefore, organic solvents are not required during the preparation process, making the delivery system much simpler. The composite hydrogel material formed using Alg, GE, and CHC will greatly improve its stability and expand its application range while retaining its pH responsiveness.

[0032] Compared with traditional Alg immobilization, the present invention retains its pH responsiveness, improves the swelling performance of the material, and the enzymatic activity of Lip. The present invention uses Alg, GE, and CHC to prepare immobilized lipase Lip-Alg / GE / CHC composite hydrogel beads, which greatly improves the defects of poor immobilization effect of Lip by Alg as an immobilization carrier and low swelling rate.

[0033] Advantages of the present invention:

[0034] 1. The Lip-Alg / GE / CHC composite hydrogel beads prepared by the present invention have a higher swelling rate, which is beneficial for the release of the entrapped Lip in the intestine.

[0035] 2. The Lip-Alg / GE / CHC composite hydrogel beads prepared by the present invention have the characteristics of simple preparation and good reproducibility. By adding appropriate amounts of GE and CHC, the disadvantage of poor immobilization effect of using Alg alone is improved, a high embedding rate and enzyme activity of Lip are achieved, the stability of Lip is improved, and it has pH responsiveness. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the embodiments are briefly introduced below.

[0037] Figure 1 This is the preparation route of composite hydrogel beads immobilizing Lip in the examples of the present invention;

[0038] Figure 2 The preparation conditions of composite hydrogel beads immobilized Lip in the present invention are optimized, wherein A is the effect of Alg concentration on the activity of immobilized Lip; B is the effect of GE concentration on the activity of immobilized Lip; C is the effect of CHC concentration on the activity of immobilized Lip; D is the effect of CaCl2 concentration on the activity of immobilized Lip;

[0039] Figure 3 is a scanning electron microscope of the immobilized carrier in the example of the present invention, wherein AC is the whole, cross-section and cross-sectional view of Alg hydrogel beads magnified 1000 times, DF is the whole, cross-section and cross-sectional view of Alg / GE hydrogel beads magnified 1000 times, and GI is the whole, cross-section and cross-sectional view of Alg / GE / CHC composite hydrogel beads magnified 1000 times;

[0040] Figure 4 is the swelling property of Alg / GE / CHC composite hydrogel beads in the examples of the present invention;

[0041] Figure 5 The pH responsiveness of Lip-Alg / GE / CHC composite hydrogel beads in the present invention. DETAILED DESCRIPTION

[0042] The present invention provides a method for preparing Lip-Alg / GE / CHC composite hydrogel beads, comprising the following steps:

[0043] 1) mixing the lipase solution with the sodium alginate solution to obtain a Lip-Alg / GE solution;

[0044] The volume ratio of the lipase solution to the sodium alginate solution is 1:4;

[0045] The lipase activity in the lipase solution is 50 U / mL;

[0046] The mass concentration of sodium alginate in the sodium alginate solution is 1.5-2.5%, and the mass concentration of gelatin is 0.1-1%;

[0047] 2) mixing the Lip-Alg / GE solution obtained in step 1) with the mixed solution, and stirring and reacting after the hydrogel beads are formed to obtain Lip-Alg / GE / CHC composite hydrogel beads;

[0048] The mixed solution is obtained by mixing a chitosan hydrochloride solution and a calcium chloride solution;

[0049] The mass concentration of the chitosan hydrochloride solution is 0.5-2%;

[0050] The mass concentration of the calcium chloride solution is 2-6%;

[0051] The volume ratio of the chitosan hydrochloride solution to the calcium chloride solution is 1:4;

[0052] The volume ratio of the mixed solution to the sodium alginate solution is 10:0.8.

[0053] The present invention mixes a lipase solution with a sodium alginate solution to obtain a Lip-Alg / GE solution; the volume ratio of the lipase solution to the sodium alginate solution is 1:4; the enzyme activity of the lipase in the lipase solution is 50U / mL; the mass concentration of sodium alginate in the sodium alginate solution is 1.5-2.5%, and the mass concentration of gelatin is 0.1-1%. In the present invention, the solvent of the lipase solution is preferably a Tris-HCl buffer solution, containing a mass concentration of 1% gum arabic and 0-4mM sodium deoxycholate, and the pH value of the Tris-HCl buffer solution is preferably 6.0-10.0, and the concentration is 0.01-1M. In the present invention, the mass concentration of sodium alginate in the sodium alginate solution is preferably 2%, and the mass concentration of gelatin is preferably 0.5%. The present invention does not specifically limit the source of the above reagents, and conventional commercially available ones can be used. In the present invention, the lipase is preferably derived from pig pancreatic lipase.

[0054] The present invention mixes the obtained Lip-Alg / GE solution with a mixed solution, and after the hydrogel beads are formed, a stirring reaction is carried out to obtain Lip-Alg / GE / CHC composite hydrogel beads; the mixed solution is obtained by mixing a chitosan hydrochloride solution and a calcium chloride solution; the mass concentration of the chitosan hydrochloride solution is 0.5-2%; the mass concentration of the calcium chloride solution is 2-6%; the volume ratio of the chitosan hydrochloride solution to the calcium chloride solution is 1:4; the volume ratio of the mixed solution to the sodium alginate solution is 10:0.8. In the present invention, the mass concentration of the chitosan hydrochloride solution is preferably 1%. In the present invention, the mass concentration of the calcium chloride solution is preferably 4%. In the present invention, the stirring reaction time is preferably 20 minutes, and the temperature is preferably 0-4°C. The present invention does not specifically limit the source of the above reagents, and conventional commercially available products can be used.

[0055] In the present invention, the mass concentration of sodium alginate in the sodium alginate solution is preferably 1.5%, and the mass concentration of gelatin is preferably 1%. In the present invention, the mass concentration of the chitosan hydrochloride solution is preferably 2%, and the mass concentration of the calcium chloride solution is preferably 6%.

[0056] In the present invention, the mass concentration of sodium alginate in the sodium alginate solution is preferably 2.5%, and the mass concentration of gelatin is preferably 1%. In the present invention, the mass concentration of chitosan hydrochloride solution is preferably 1%, and the mass concentration of calcium chloride solution is preferably 2%.

[0057] In the present invention, the mass concentration of sodium alginate in the sodium alginate solution is preferably 2%, and the mass concentration of gelatin is preferably 0.5%. In the present invention, the mass concentration of the chitosan hydrochloride solution is preferably 1%, and the mass concentration of the calcium chloride solution is preferably 4%.

[0058] The present invention also provides Lip-Alg / GE / CHC composite hydrogel beads prepared by the preparation method described in the above technical solution.

[0059] The present invention also provides the use of the Lip-Alg / GE / CHC composite hydrogel beads described in the above technical solution in improving the swelling performance of the hydrogel beads.

[0060] The present invention also provides the use of the Lip-Alg / GE / CHC composite hydrogel beads described in the above technical solution in improving the lipase activity of the hydrogel beads.

[0061] In the embodiment, the calculation formula of relative enzyme activity (RelativeActivity) is as follows:

[0062]

[0063] In the embodiment, the calculation formula of the swelling degree is as follows:

[0064]

[0065] In the embodiment, the calculation formula of enzyme activity recovery rate is as follows:

[0066]

[0067] In order to further illustrate the present invention, the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0068] Example 1

[0069] Preparation of Lip-Alg / GE / CHC composite hydrogel beads

[0070] Preparation steps: Figure 1 As shown, first take 200 μL of Lip solution (enzyme activity is 50 U / mL) and add it to 800 μL of Alg / GE mixed solution, then take 2 mL of CHC solution and add it to 8 mL of CaCl2 solution and mix well. Use a syringe to absorb the Lip-Alg / GE mixed solution and slowly drip it vertically into the mixed solution of CHC and CaCl2 at a distance of 10 cm from the beaker. After the hydrogel beads are formed, use a glass rod to gently stir to avoid adhesion of the hydrogel beads. After cross-linking at 0-4°C for 20 minutes, remove the hydrogel beads and rinse off the excess CHC and CaCl2 solution on the surface with distilled water to obtain Lip-Alg / GE / CHC composite hydrogel beads.

[0071] Selection of concentration of each substance

[0072] 1.1 Selection of Alg concentration

[0073] When exploring the relationship between Alg concentration and enzyme activity, the GE concentration in the Alg / GE mixed solution was 1% (w / v), the concentration of the CHC solution was 1% (w / v), the concentration of the CaCl2 solution was 2% (w / v), the ratio of the enzyme to the Alg / GE gel mixed solution was 1:4 (v:v), the ratio of the CHC solution to the CaCl2 solution was 1:4 (v:v), the ratio of the CHC / CaCl2 mixed solution to the Alg / GE mixed solution was 10:0.8 (v:v), the reaction time of the Lip-Alg / GE mixed solution and the CHC / CaCl2 mixed solution was 20 min, and the reaction temperature was 0-4°C. The Alg concentrations in the Alg / GE mixed solution were 1.5% (w / v), 2.0% (w / v) and 2.5% (w / v), respectively. The immobilized enzyme was placed in a 4°C refrigerator for standby use.

[0074] The experimental results are as follows Figure 2 As shown in Figure A, it can be found that the relative activity of the immobilized enzyme increases with the increase of Alg concentration, and the relative activity reaches the highest when the Alg concentration is 2% (w / v). As the concentration of Alg continues to increase, the relative activity of the enzyme tends to decrease. This result is because the composite hydrogel beads formed at low concentrations of Alg have a loose structure, resulting in more enzyme leakage, and as the concentration of Alg increases, the structure becomes more and more compact, thereby improving the fixation effect of the immobilized enzyme. However, when the concentration of Alg is too high, the solution is too viscous, which can easily cause the syringe to be blocked, and the structure is too dense, which hinders the contact between the enzyme and the substrate molecules, thereby reducing the activity.

[0075] 1.2 Selection of GE concentration

[0076] When exploring the relationship between GE concentration and enzyme activity, the Alg concentration in the Alg / GE mixed solution was 2% (w / v), the CHC concentration was 1% (w / v), the CaCl2 concentration was 2% (w / v), the enzyme and the Alg / GE gel mixed solution ratio was 1:4 (v:v), the CHC solution and the CaCl2 solution ratio was 1:4 (v:v), the CHC / CaCl2 mixed solution and the Alg / GE mixed solution ratio was 10:0.8 (v:v), the Lip-Alg / GE mixed solution and the CHC / CaCl2 mixed solution reaction time was 20min, and the reaction temperature was 0-4°C. The GE concentrations in the Alg / GE mixed solution were 0.1% (w / v), 0.5% (w / v), and 1% (w / v). The immobilized enzyme was placed in a 4°C refrigerator for standby use.

[0077] The experimental results are as follows Figure 2 As shown in B, the addition of GE increased the enzyme activity on the basis of Alg. When the GE concentration ranged from 0.5% (w / v) to 1% (w / v), the relative activity of the enzyme was greater than 90%, indicating that GE at nearby concentrations can increase the relative activity of the enzyme. In this study, a GE concentration of 0.5% (w / v) was selected.

[0078] 1.3 Selection of CHC concentration

[0079] When exploring the relationship between CHC concentration and enzyme activity, the Alg concentration in the Alg / GE mixed solution was 2% (w / v), the GE concentration was 0.5% (w / v), the CaCl2 concentration was 2% (w / v), the enzyme and Alg / GE gel mixed solution ratio was 1:4 (v:v), the CHC solution and CaCl2 solution ratio was 1:4 (v:v), the CHC / CaCl2 mixed solution and the Alg / GE mixed solution ratio was 10:0.8 (v:v), the Lip-Alg / GE mixed solution and the CHC / CaCl2 mixed solution reaction time was 20min, and the reaction temperature was 0-4°C. The CHC concentrations were 0.5% (w / v), 1% (w / v) and 2% (w / v), respectively. The immobilized enzyme was placed in a 4°C refrigerator for standby use.

[0080] The experimental results are as follows Figure 2 As shown in Figure C, on the basis of Alg and GE, adding CHC can improve the relative activity of the enzyme. The enzyme activity reaches the highest when the CHC concentration is 1% (w / v), and the enzyme activity decreases when the CHC concentration is 2% (w / v). The principle is similar to the relationship between Alg concentration and enzyme relative activity. When the CHC concentration is low, the structure of the composite hydrogel beads is relatively loose, and as the CHC concentration increases, the structure of the composite hydrogel beads becomes too tight, which hinders the contact between the enzyme and the substrate, resulting in low relative activity of the immobilized enzyme.

[0081] 1.4 Selection of CaCl2 concentration

[0082] When exploring the relationship between CaCl2 concentration and enzyme activity, the Alg concentration in the Alg / GE mixed solution was 2% (w / v), the GE concentration was 0.5% (w / v), the CHC concentration was 1% (w / v), the ratio of enzyme to Alg / GE gel mixed solution was 1:4 (v:v), the ratio of CHC solution to CaCl2 solution was 1:4 (v:v), the ratio of CHC / CaCl2 mixed solution to Alg / GE mixed solution was 10:0.8 (v:v), the reaction time of Lip-Alg / GE mixed solution and CHC / CaCl2 mixed solution was 20min, and the reaction temperature was 0-4°C. The CaCl2 concentrations were 2% (w / v), 4% (w / v) and 6% (w / v), respectively. The immobilized enzyme was placed in a 4°C refrigerator for standby use.

[0083] The experimental results are as follows Figure 2As shown in D, the relative activity of the enzyme reaches the highest when the CaCl2 concentration is 4% (w / v). When the CaCl2 concentration is low, the structure of the composite hydrogel beads is loose, and the enzyme molecules leak. As the concentration of CaCl2 increases, the structure of the composite hydrogel beads becomes tight, which significantly increases the relative activity of the immobilized enzyme. However, when the concentration of CaCl2 is 6% (w / v), the enzyme activity decreases, indicating that the gaps in the composite hydrogel beads formed by the reaction of too high a concentration of CaCl2 with Alg are too small, and the substrate cannot smoothly pass through the gaps to react with the enzyme, resulting in a decrease in enzyme activity.

[0084] 1.5 Orthogonal experiment to optimize the preparation of Lip-Alg / GE / CHC composite hydrogel beads

[0085] According to the results of the single factor experiment, four factors including Alg concentration, GE concentration, CHC concentration and CaCl2 solution concentration in Alg / GE / CHC composite hydrogel beads were selected, and the enzyme activity recovery rate of immobilized Lip was used as the evaluation index to design an orthogonal experiment. The levels of orthogonal experimental factors are shown in Table 1.

[0086] Table 1 Factor levels of orthogonal experiment for optimization of Lip immobilization conditions

[0087]

[0088] Table 2 Results and analysis of orthogonal experiments for optimization of Lip immobilization conditions

[0089]

[0090]

[0091] The experimental results are shown in Table 2. The preparation processes of the best immobilized lipase are A1B3C3D3 and A3B3C2D1. A1B3C3D3 is selected as the best combination from the perspective of cost reduction and efficiency improvement. The Alg concentration in the immobilized carrier prepared by the best combination is 1.5% (w / v), the GE concentration is 1% (w / v), the CHC concentration is 2% (w / v), and the CaCl2 solution concentration is 6% (w / v) for verification tests, and the enzyme activity recovery rate can reach 90.18%.

[0092] Example 2

[0093] Characterization of Alg / GE / CHC composite hydrogel beads

[0094] 2.1 Scanning electron microscopy of Alg / GE / CHC composite hydrogel beads

[0095] In this example, the immobilized material was characterized using a scanning electron microscope, as follows:

[0096] Take 200 μL of Tris-HCl (pH = 7.4) buffer and add it to 800 μL of 2% Alg (w / v) solution to obtain Alg solution. Use a syringe to drop the Alg solution into 10 mL of 4% CaCl2 (w / v) solution. After the hydrogel beads are formed, use a glass rod to gently stir to prevent the hydrogel beads from sticking. After reacting at 0-4°C for 20 minutes, remove the hydrogel beads and rinse them with distilled water to obtain Alg hydrogel beads.

[0097] Take 200 μL of Tris-HCl buffer and add it to 800 μL of 2% Alg (w / v) and 0.5% GE (w / v) mixed solution to obtain Alg / GE mixed solution. Use a syringe to drop the obtained Alg / GE mixed solution into 10 mL of 4% CaCl2 (w / v) solution. After the hydrogel beads are formed, use a glass rod to gently stir to avoid adhesion of the hydrogel beads. After reacting at 0-4°C for 20 minutes, remove the hydrogel beads and rinse them with distilled water to obtain Alg / GE hydrogel beads.

[0098] Take 200 μL of Tris-HCl buffer and add it to 800 μL of 2% Alg (w / v) and 0.5% GE (w / v) mixed solution to obtain Alg / GE mixed solution. Then take 2 mL of 1% CHC (w / v) solution, add 8 mL of 4% CaCl2 (w / v) solution, and mix well. Use a syringe to drop the obtained Alg / GE mixed solution into the CHC and CaCl2 mixed solution. After the hydrogel beads are formed, use a glass rod to gently stir to avoid adhesion of the hydrogel beads. After reacting at 0-4°C for 20 minutes, remove the hydrogel beads and rinse off the excess CHC and CaCl2 solution on the surface with distilled water to obtain Alg / GE / CHC composite hydrogel beads.

[0099] After the three hydrogel beads (Alg, Alg / GE and Alg / GE / CHC) were freeze-dried in a freeze dryer, a portion of the samples was cut open, coated with a thermal evaporation integrated coating machine, and then their morphology was observed using a field emission scanning electron microscope.

[0100] The results are as follows Figure 3 As shown in the figure, during the freeze-drying process, due to the partial collapse and shrinkage of the hydrogel network during the dehydration process, the shape of the hydrogel beads is not completely spherical, and some wrinkles and cracks are formed. Compared with the Alg hydrogel beads, the surface of the Alg / GE hydrogel beads is smoother, but the internal wrinkles are more prominent, which may be the result of the interaction between Alg and GE. More protrusions and wrinkles can be seen on the surface of the Alg / GE / CHC hydrogel beads, and the addition of CHC makes the interior of the composite hydrogel beads more porous and dense.

[0101] 2.2 Swelling properties of Alg / GE / CHC composite hydrogel beads

[0102] Repeat the steps of Example 2.1 to prepare hydrogel beads of three different materials, and freeze-dry them all. Weigh 0.5 g of Alg dried hydrogel beads, Alg / GE dried hydrogel beads, and Alg / GE / CHC dried hydrogel beads, respectively, add 1 mL of Tris-HCl buffer, take out the microbeads after the same interval, use absorbent paper to absorb the buffer on the surface, and then place them on an electronic balance to weigh their mass. Add the same volume of buffer, measure continuously for 8 hours, and calculate and compare the swelling rate of hydrogel beads of different materials.

[0103] The swelling degree of the hydrogel beads is closely related to the release mechanism and kinetics of digestive enzymes. As the swelling rate increases, the pore size in the gel network becomes larger, thereby promoting the diffusion of Lip from the inside of the beads to the outside. The swelling rate experimental results are shown in Figure 2. Figure 4 As shown in the figure, compared with Alg hydrogel beads, the swelling rates of Alg / GE hydrogel beads and Alg / GE / CHC composite hydrogels increased significantly. Among them, the swelling rate of Alg / GE / CHC composite hydrogel beads was the highest, which was significantly different from the swelling rates of the other two hydrogel beads. It may be because the addition of GE and CHC increased the volume of the hydrogel beads to varying degrees, making them have stronger water absorption capacity. In addition, due to the interaction between the carboxylic acid groups of Alg and CHC, these groups were ionized, thereby absorbing water, resulting in a high swelling rate.

[0104] Example 3

[0105] Characterization of the properties of immobilized Lip

[0106] 3.1 Evaluation of the enzymatic properties of Lip-Alg / GE / CHC composite hydrogel beads

[0107] Take 200 μL of Lip solution (enzyme activity is 50 U / mL) and add it to 800 μL of 2% Alg (w / v) solution to obtain Lip-Alg mixed solution. Use a syringe to drop the Lip-Alg mixed solution into 10 mL of 4% CaCl2 (w / v) solution. After the hydrogel beads are formed, use a glass rod to gently stir to avoid adhesion of the hydrogel beads. After reacting at 0-4°C for 20 minutes, remove the hydrogel beads and rinse them with distilled water to obtain Lip-Alg hydrogel beads.

[0108] Take 200 μL of Lip solution (enzyme activity is 50 U / mL) and add it to 800 μL of 2% Alg (w / v) and 0.5% GE (w / v) mixed solution to obtain Lip-Alg / GE mixed solution. Use a syringe to drop the Lip-Alg / GE mixed solution into 10 mL of 4% CaCl2 (w / v) solution. After the hydrogel beads are formed, use a glass rod to gently stir to avoid adhesion of the hydrogel beads. After reacting at 0-4°C for 20 minutes, remove the hydrogel beads and rinse them with distilled water to obtain Lip-Alg / GE hydrogel beads.

[0109] Take 200 μL of Lip solution (enzyme activity is 50 U / mL) and add it to 800 μL of 2% Alg (w / v) and 0.5% GE (w / v) mixed solution to obtain Lip-Alg / GE mixed solution. Then take 2 mL of 1% CHC (w / v) solution, add 8 mL of 4% CaCl2 (w / v) solution, and mix well. Use a syringe to drop the Lip-Alg / GE mixed solution into the CHC and CaCl2 mixed solution. After the hydrogel beads are formed, use a glass rod to gently stir to avoid adhesion of the hydrogel beads. After reacting at 0-4°C for 20 minutes, remove the hydrogel beads and rinse off the excess CHC and CaCl2 solution on the surface with distilled water to obtain Lip-Alg / GE / CHC composite hydrogel beads.

[0110] The recovery rate of the enzyme activity of Lip was tested, and immobilized Lip hydrogel beads (Lip-Alg, Lip-Alg / GE and Lip-Alg / GE / CHC) were prepared using Alg, Alg / GE and Alg / GE / CHC as materials. Since sodium citrate can replace the calcium ions in the calcium alginate formed by Alg and CaCl2. Therefore, sodium citrate was used to dissolve the above hydrogel beads, so that all the Lip embedded in the hydrogel beads leaked out. Then, the free enzyme with the same enzyme activity was used as a control, and the substrate was added for the same reaction time, and its absorbance was measured.

[0111] Table 3 Comparison of enzymatic properties of immobilized enzymes

[0112] Immobilized enzyme Enzyme activity recovery rate (%) Lip-Alg hydrogel beads 31.18±3.15 Lip-Alg / GE composite hydrogel beads 57.18±5.55 Lip-Alg / GE / CHC composite hydrogel beads 98.93±0.59

[0113] The results are shown in Table 3. The enzyme activity recovery rate of Lip-Alg hydrogel beads was 31.18±3.15%, the enzyme activity recovery rate of Lip-Alg / GE composite hydrogel beads was 57.18±5.55%, and the enzyme activity recovery rate of Lip-Alg / GE / CHC composite hydrogel beads was 98.93±0.59%. Compared with the other two hydrogel beads, Lip-Alg / GE / CHC composite hydrogel beads had a higher enzyme activity recovery rate.

[0114] 3.2 pH responsiveness of Lip-Alg / GE / CHC composite hydrogel beads

[0115] Take 200 μL of Lip solution (enzyme activity is 50 U / mL) and add it to 800 μL of 2% Alg (w / v) and 0.5% GE (w / v) mixed solution to obtain Lip-Alg / GE mixed solution. Then take 2 mL of 1% CHC (w / v) solution, add 8 mL of 4% CaCl2 (w / v) solution, and mix evenly. Use a syringe to drop the Lip-Alg / GE mixed solution into the CHC and CaCl2 mixed solution. After the hydrogel beads are formed, use a glass rod to gently stir to avoid adhesion of the hydrogel beads. After reacting at 0-4°C for 20 minutes, remove the hydrogel beads and rinse off the excess CHC and CaCl2 solution on the surface with distilled water to obtain Lip-Alg / GE / CHC composite hydrogel beads. Place the Lip-Alg / GE / CHC composite hydrogel beads in different pH environments (pH=2.0, pH=7.4) and measure the enzyme activity after the reaction.

[0116] The results are as follows Figure 5 As shown, Lip-Alg / GE / CHC composite hydrogel beads have a certain pH responsiveness. The enzyme activity of the immobilized enzyme in Lip-Alg / GE / CHC composite hydrogel beads is less than 40% of the catalytic activity at pH = 7.4 under the condition of pH = 2.0. Lip-Alg / GE / CHC composite hydrogel beads are more suitable for use in a neutral to alkaline environment, and are not suitable for reactions in an acidic environment.

[0117] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing Lip-Alg / GE / CHC composite hydrogel beads, characterized in that: The following steps are involved: 1) mixing the lipase solution with the sodium alginate solution to obtain a Lip-Alg / GE solution; The volume ratio of the lipase solution to the sodium alginate solution is 1:4; The lipase activity in the lipase solution is 50 U / mL; The mass concentration of sodium alginate in the sodium alginate solution is 1.5-2.5%, and the mass concentration of gelatin is 0.1-1%; 2) mixing the Lip-Alg / GE solution obtained in step 1) with the mixed solution, and stirring and reacting after the hydrogel beads are formed to obtain Lip-Alg / GE / CHC composite hydrogel beads; The mixed solution is obtained by mixing a chitosan hydrochloride solution and a calcium chloride solution; The mass concentration of the chitosan hydrochloride solution is 0.5-2%; The mass concentration of the calcium chloride solution is 2-6%; The volume ratio of the chitosan hydrochloride solution to the calcium chloride solution is 1:4; The volume ratio of the mixed solution to the sodium alginate solution is 10:0.

8.

2. The preparation method according to claim 1, characterized in that: In the step 1), the mass concentration of sodium alginate in the sodium alginate solution is 2%, and the mass concentration of gelatin is 0.5%.

3. The preparation method according to claim 1, characterized in that: The mass concentration of the chitosan hydrochloride solution in step 2) is 1%; The mass concentration of the calcium chloride solution is 4%.

4. The preparation method according to claim 1, characterized in that: In the step 1), the mass concentration of sodium alginate in the sodium alginate solution is 1.5%, and the mass concentration of gelatin is 1%; The mass concentration of the chitosan hydrochloride solution in step 2) is 2%, and the mass concentration of the calcium chloride solution is 6%.

5. The preparation method according to claim 1, characterized in that: In the step 1), the mass concentration of sodium alginate in the sodium alginate solution is 2.5%, and the mass concentration of gelatin is 1%; The mass concentration of the chitosan hydrochloride solution in step 2) is 1%, and the mass concentration of the calcium chloride solution is 2%.

6. The preparation method according to claim 1, characterized in that: In the step 1), the mass concentration of sodium alginate in the sodium alginate solution is 2%, and the mass concentration of gelatin is 0.5%; The mass concentration of the chitosan hydrochloride solution in step 2) is 1%, and the mass concentration of the calcium chloride solution is 4%.

7. The preparation method according to claim 1, characterized in that: The stirring reaction time of step 1) is 20 minutes, and the temperature is 0-4°C.

8. Lip-Alg / GE / CHC composite hydrogel beads prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the Lip-Alg / GE / CHC composite hydrogel beads according to claim 8 in improving the swelling properties of hydrogel beads.

10. Use of the Lip-Alg / GE / CHC composite hydrogel beads according to claim 8 in improving the activity of the hydrogel beads against lipase.